How to keep your research project on track insights from when things go wrong - edited by Keith Townsend (Cheltenham Edward Elgar Publishing, 2018)
Textbooks and journal articles on research methods are rarely of help regarding what to do when your research project goes off track. This book addresses this important, and usually hidden, aspect of research by providing students and researchers with insider insights, advice and lessons about the difficulties in the research process. Written by experienced researchers, PhD supervisors and examiners, it should prepare the reader for all that can go wrong when researching a PhD or any large research project.
Includes bibliographical references and index.
Keywords: Research--Methodology